A trapped field of 14.3 T in Y–Ba–Cu–O bulk superconductors fabricated by buffer-assisted seeded infiltration and growth. (22nd October 2018) - Namburi, Devendra K; Durrell, John H; Jaroszynski, Jan; Shi, Yunhua; Ainslie, Mark; Huang, Kaiyuan; Dennis, Anthony R; Hellstrom, Eric E; Cardwell, David A
Abstract: The two-step top seeded infiltration and growth (TSIG) melt process has emerged as a successful and reliable technique for the fabrication of single grain (RE)Ba2 Cu3 O7− δ (where RE is a rare-earth element or yttrium) bulk high temperature superconductors with engineered microstructures that exhibit improved superconducting properties. In this study, the performance of these materials in large applied magnetic fields has been investigated by field cooling single grain samples in a magnetic field of 18 T. YBa2 Cu3 O7− δ samples processed without added Ag by the TSIG technique, in the two-sample stack configuration, trapped a magnetic field of 14.3 T at 28 K after field cooling from 100 K and subsequent removal of the applied field. This result is particularly significant in that, previously, only single grain (RE)Ba2 Cu3 O7− δ bulk superconductors containing Ag have been reported to be able to tolerate the large stresses on the samples inherent in the magnetisation process at large fields. The samples prepared in the present study were pre-stressed using a reinforcing stainless-steel ring, although, otherwise, they did not contain any additives, dopants or resin impregnation. The ability of samples processed by TSIG to withstand large tensile forces without Ag addition is attributed to the reduced incidence of intrinsic cracks/pores in the single grain microstructure.